Functional Identification and Characterization of Leucokinin and Its Receptor in the Fall Webworm, Hyphantria cunea - Sun, Lili; Ma, Heting; Gao, Yuan; Wang, Zhiying; Cao, Chuanwang (Frontiers in Physiology, 2021)
Neuropeptides function as central neuromodulators and circulating hormones that modulate insect behavior and physiology. Leucokinin (LK) is an intercellular signaling molecule that mediates many physiological and behavioral processes. However, the functions of LK associated with environmental stress and feeding behavior in the fall webworm, Hyphantria cunea, is little known. Our primary objective is to understand the function of LK and LK receptor (LKR) neuroendocrine system in H. cunea. In the present study, the results showed that LK/LKR are expressed at different developmental stages and in various tissues of H. cunea. A candidate receptor–ligand pairing for LK was identified in the larval transcriptome of H. cunea. In a heterologous expression system, the calcium assay was used to demonstrate that LKR is activated by HcLKs in a dose-dependent manner, with 50% effective concentration (EC50) values of 8.44–90.44nM. Knockdown of HcLK and HcLKR by microinjecting target-specific dsRNA leads to several effects in H. cunea, including feeding promotion, increase in resistance to desiccation and starvation stress, and regulation of water homeostasis. The transcript levels of HILP2 (except in the LK knockdown group), HILP5, and HILP8 increased, whereas those of HILP3, HILP4, and HILP6 decreased; HILP1, HILP2 (in the LK knockdown group), and HILP7 gene expression was not influenced after LK and LKR knockdown. Variations in mRNA expression levels in insulin-like peptide genes in the knockdown larvae suggest an essential role of these genes in survival in H. cunea. To our knowledge, the present study is the first comprehensive study of LK and LKR – from gene to behavior – in H. cunea.